A MODEL FOR DEVELOPING SOFT SKILL TRAINING MANAGEMENT ORIENTED TOWARD SERVICE QUALITY FOR SHS COUSELORS - Endang Rasmani, Upik Elok; Widodo, Joko; Wibowo, Mungin Edy (The Journal of Educational Development, 2017)
As a way to achieve a high-quality Guidance and Counseling (GC) session, there is a need to apply soft skills in GC service interactions. However, many counselors have yet to optimally develop and implement proper soft skills in GC service sessions. Therefore, a model for developing soft skills training management oriented toward service quality is required for counselors. This is particularly necessary because a meaningful relationship between counselors and students can be built through having proficient soft skills, such as appearance, verbal communication skills, work ethics, analytical abilities, self-management, and others. The purpose of this study is to obtain ways to overcome hindrances in soft skill training programs, so similar service quality improvement programs for counselors could be carried out well. This study proposes a model for developing soft skills training management oriented toward service quality for counselors. Training management includes planning, organizing, implementatoin, monitoring and evaluation, whereas the conceptual model for soft skill training oriented toward service quality consists of training analysis, training program design, training development, training implementation, and training evaluation.